Public service vouchers - Colin, Frederic (2005)
The public voucher system is a means of paying for a given public service. Couchers are issued by the public authorities to individual users to enable them to gain access to any institution that is approved by the public authorities, for a specific purpose. The provider of the service is paid back the amount of the voucher by the public institution that provides the funding for the voucher. This system provides a means of reviewing the relationship between the user and the public service in terms of efficiency and freedom. The voucher system is designed to improve competition among public service providers and to make public service offerings more flexible. While it does offer some interesting possibilities in terms of diversification of the services on offer, nonetheless the voucher system poses certain risks. In particular, it may lead to community behaviour patterns among beneficiaries and undermine equal opportunity. In any case, as the voucher system brings closer together the practical arrangments for defraying services in the private and public sectors, it opens up some useful avenues of reflection for the modernization of public services. - Reproduced.
Keywords: Public administration